High MYC Levels Favour Multifocal Carcinogenesis - Sollazzo, Manuela; Genchi, China; Paglia, Simona; Di Giacomo, Simone; Pession, Annalisa; de Biase, Dario; Grifoni, Daniela (Frontiers in Genetics, 2018)
The term “field cancerisation” describes the formation of tissue sub-areas highly susceptible to multifocal tumourigenesis. In the earlier stages of cancer, cells may indeed display a series of molecular alterations that allow them to proliferate faster, eventually occupying discrete tissue regions with irrelevant morphological anomalies. This behaviour recalls cell competition, a process based on a reciprocal fitness comparison: when cells with a growth advantage arise in a tissue, they are able to commit wild-type neighbours to death and to proliferate at their expense. It is known that cells expressing high MYC levels behave as super-competitors, able to kill and replace less performant adjacent cells; given MYC upregulation in most human cancers, MYC-mediated cell competition is likely to pioneer field cancerisation. Here we show that MYC overexpression in a subterritory of the larval wing epithelium of Drosophila is sufficient to trigger a number of cellular responses specific to mammalian pre-malignant tissues. Moreover, following induction of different second mutations, high MYC-expressing epithelia were found to be susceptible to multifocal growth, a hallmark of mammalian pre-cancerous fields. In summary, our study identified an early molecular alteration implicated in field cancerisation and established a genetically amenable model which may help study the molecular basis of early carcinogenesis.